Peningkatan Pengetahuan Masyarakat Tentang Bersihan Jalan Nafas Pada Pasien Bronchitis - Sinuraya, Elida; Idahwati, Idahwati; Sijabat, Flora; Halawa, Theresia; Halawa, Alias (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: Bronchitis is an inflammation of the respiratory tract. Sputum in the airways can cause airway obstruction and result in respiratory failure. Knowledge about maintaining airway clearance in bronchitis patients and their families is crucial. Objective: to increase public knowledge about maintaining airway clearance in bronchitis patients. Method:This community service method is to use the lecture and question and answer method for bronchitis patients and their families who come to Sari Mutiara Hospital in October 2024 Result: 80% of the public were able to state the definition of bronchitis, 42% were able to explain the signs and symptoms of bronchitis, and 58% of the public were able to explain maintaining airway clearance in bronchitis patients Conclusion: After receiving teaching,  public knowledge about airway maintenance  increased.